Entrepreneurship in Meat Processing - Muthukumar, Muthukumar (Indian Farming, 2020)
Meat sector is an integral and important component of agro-food industry in India, which contributes immensely for nutritional security, employment generation and earning much required foreign exchange. India produces about 8.1 million tonnes of meat annually (DADF, 2019). Around 72% of Indians are now on non-vegetarian dietary habit and regular meat consumption has rigorously increased over the years. Holding 11.6% of world livestock population and 17.71% of the world human population, India has tremendous potential in meat production, processing and marketing. The Indian meat market was valued close to USD 30 billion and is one of the fastest growing industry at a CAGR of 22% (Mintel Industry Research Report, 2017). Rapid consolidation in meat processing, more vertical integration and large number of smaller processing units will be the key trends in future.